Sex differences in clinical characteristics, timeliness of care, and in-hospital outcomes of adult non-trauma patients in the emergency department - Kun-Chuan Chen; Ji-Ze Hsu; Shu-Hui Wen (PLoS ONE, 2025)
Background Data on sex differences in the clinical characteristics and outcomes of unselected emergency department (ED) patients are limited. We conducted a retrospective real-world cohort study to evaluate sex differences in clinical characteristics, ED timeliness of care, and in-hospital outcomes of adult non-trauma ED patients. Methods Data from adult non-trauma patients who paid their first ED visit to a tertiary medical center from January 2018 to Jun 2020 were retrospectively analyzed. The patients were divided into male and female cohorts. The ED length of stay (LOS) was measured as the outcome of timeliness of care, whereas hospital admission, hospital LOS, and in-hospital mortality were measured as the in-hospital outcomes. Multivariate regression analyses were utilized to investigate the association between sex and outcomes. Results Of the 43,661 patients included, 49.2% were males. The male cohort was older and had higher incidences of interhospital transfer and Taiwan Triage and Acuity Scale (TTAS) levels 1 and 2, higher mean Charlson comorbidity index, and more comorbidities than the female cohort. The male cohort had longer ED LOS and hospital LOS and higher incidences of hospital admission and in-hospital mortality. Multivariate regression analyses revealed that the male sex was an independent risk factor associated with adverse outcomes after adjustment for confounding factors. All these adverse outcomes were found in the male subgroup with TTAS levels 1–3. Conclusions Our study identified sex differences in clinical characteristics, ED timeliness of care, and in-hospital outcomes of adult non-trauma ED patients. Male patients had various unfavorable conditions, including having older age, higher acuity levels, and more comorbidities, and were at higher unadjusted and adjusted risk for adverse outcomes on ED LOS, hospital admission, hospital LOS, and in-hospital mortality. The male subgroup with TTAS levels 1–3 was vulnerable to the negative impact of sex on these outcomes.